Effects of empagliflozin on left ventricular diastolic function in addition to usual care in individuals with type 2 diabetes mellitus—results from the randomized, double-blind, placebo-controlled EmDia trial - Prochaska, Jürgen H.; Jünger, Claus; Schulz, Andreas; Arnold, Natalie; Müller, Felix; Heidorn, Marc William; Baumkötter, Rieke; Zahn, Daniela; Koeck, Thomas; Tröbs, Sven-Oliver; Lackner, Karl J.; Daiber, Andreas; et al. (Clinical research in cardiology, 2023)
Background The sodium-glucose co-transporter 2 inhibitor empagliflozin improves cardiovascular outcome in patients with type 2 diabetes mellitus (T2DM) and heart failure. Experimental studies suggest a direct cardiac effect of empagliflozin associated with an improvement in left ventricular diastolic function. Methods In the randomized, double-blind, two-armed, placebo-controlled, parallel group trial EmDia, patients with T2DM and elevated left ventricular E / E ´ ratio were enrolled and randomized 1:1 to receive empagliflozin 10 mg/day versus placebo. The primary endpoint was the change of left ventricular E / E ´ ratio after 12 weeks of intervention. Results A total of 144 patients with T2DM and an elevated left ventricular E / e ´ ratio (age 68.9 ± 7.7 years; 14.1% women; E / e ´ ratio 9.61[8.24/11.14], left ventricular ejection fraction 58.9% ± 5.6%). After 12 weeks of intervention, empagliflozin resulted in a significant higher decrease in the primary endpoint E / e ´ ratio by − 1.18 ([95% confidence interval (CI) − 1.72/− 0.65]; P < 0.0001) compared with placebo. The beneficial effect of empagliflozin was consistent across all subgroups and also occurred in subjects with heart failure and preserved ejection fraction ( n = 30). Additional effects of empagliflozin on body weight, HbA1c, uric acid, red blood cell count, hemoglobin, mean corpuscular hemoglobin, and hematocrit were detected (all P < 0.001). Approximately one-third of the reduction in E / e ´ by empagliflozin could be explained by the variables examined. Conclusions Empagliflozin improves diastolic function in patients with T2DM and elevated end-diastolic pressure. Since the positive effects were consistent in patients with and without heart failure with preserved ejection fraction, the data add a mechanistic insight for the beneficial cardiovascular effect of empagliflozin. Trial registration Clinicaltrials.gov, unique identifier: NCT02932436. Graphical abstract